Derivatives of 3-(alkylthio)-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-4-amines as increasing efficiency substances - Andrey Safonov (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2018)
In today's society, especially in eastern countries such as China, Japan etc., the problem of fatigue and even death at work is acute. One of the solution to this problem is complex therapy with increasing efficiency drugs. Derivatives of 1,2,4-triazole have already proven themselves as potential compounds for pharmacological correction of fatigue. Compounds were synthesized at the Department of toxicological and inorganic chemistry ZSMU. Using method of forced swimming on a group of white nonlinear rats activity of anti-fatigue of the compounds were analyzed. Having analyzed the data of pharmacological correction of fatigue for 3-(alkylthio)-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-4-amines, it should be noted that this series of compound do not show anti-fatigue effect. Introduction in molecule 3- (nonylthio)-5-(thiophen-2-ylmethyl)-4H- 1, 2, 4-triazol-4-amine 4-fluorbenzylidene, 4-(dimethylamino) benzylidene, 4- methoxybenzylidene, 2-chloro-6-fluorobenzylidene radicals lead to increase actoprotective effect. The most active compound is N-(2-chloro-6-fluorobenzylidene)-3-(nonylthio)-5-(thiophen- 2- ylmethyl)- 4H- 1, 2, 4- triazol- 4-amine which exceeds the standard (riboxin).